Muon neutrino and antineutrino cross sections & neutrino detector readout - Batchelor, Charlie (The University of Edinburgh, 2025)
The Micro-scale Booster Neutrino Experiment is a ground-level Liquid Argon Time Projection Chamber neutrino detector, which collected data from the Booster Neutrino Beam and coincidentally, the Neutrinos at the Main Injector accelerator neutrino beam at Fermilab. The Deep Underground Neutrino Experiment is a next generation neutrino detector experiment that aims to provide answers to several critical questions posed by the current Standard Model of particle physics. This thesis will explore the use of Machine Learning techniques to extract interesting physics events from Liquid Argon Time Projection Chambers. It presents an investigation into the online triggering of data readout, using a prototype DUNE far detector, based at CERN. An attempt to separate an admixture of muon neutrinos and antineutrinos arriving at the MicroBooNE detector from the NuMI flux is also presented. The analysis then proceeds to extract charged current cross sections for the separated neutrino and antineutrino charged current interactions on argon nucleons. An understanding of these interactions is critical to a successful DUNE physics campaign.
Keywords: neutrinos; MicroBooNE; DUNE; machine learning; matter and antimatter neutrinos; argon atom interaction